The Association between a 24-Hour Blood Pressure Pattern and Circadian Change in Plasma Aldosterone Concentration for Patients with Aldosterone-Producing Adenoma. (29th July 2019) - Li, Hai; Liu, Jianbin; Liu, Juan; Liu, Liehua; Huang, Minmin; Wei, Guohong; Deng, Wanping; Huang, Zhimin; Cao, Xiaopei; Xiao, Haipeng; Li, Yanbing
Abstract : The absence of nocturnal blood pressure (BP) decline is associated with hypertensive complications. Data regarding circadian BP patterns in patients with aldosterone-producing adenoma (APA) are limited and equivocal. We evaluated the circadian BP profile in patients with APA and its relationship with the circadian aldosterone rhythm. BP in patients with APA and in those with essential hypertension (EH) were assessed through in-hospital 24-h ambulatory blood pressure monitoring. Over a 24-h in-hospital period, plasma aldosterone levels taken at midnight, 0400, 0800, 1200, 1600, and 2000 h were measured. To evaluate a correlation between BP and hormone rhythm, we included 27 patients with APA (APA group) and 27 patients with EH (EH group). Both groups had similar age, sex ratio, body mass index, duration of hypertension, family history of hypertension, and lipid profiles. The day-night BP differences in both patient groups were similar, whether expressed as absolute values or percentages. The proportions of patients with dipping BP profiles were also comparable (APA group, 5 of 27; EH group, 7 of 27; χ 2 = 0.429; P = 0.513). At each time point, APA group plasma aldosterone concentrations (PACs) were higher than those of the EH group. A circadian change in relation to PAC was observed in both groups. A correlation between PAC and BP was statistically nonsignificant in most study patients in either group. Our data indicated that the circadian BP pattern was not associated with a change in PAC levels in patients with APA.